Delayed Speech Dengan dan Tanpa Gangguan Pendengaran pada Anak Usia 6 Bulan sampai 3 Tahun di Jala Puspa RSPAL Dr. Ramelan Surabaya Periode 2017-2020 - Halim, Anthony Stephen; Limantara, Edward; Diarsvitri, Wienta (Faculty of Medicine, Universitas Andalas, 2021)
Late or untreated delayed speech can be a risk for social, emotional, behavioral and cognitive problems in adulthood. Delayed speech is associated with hearing loss, mental retardation, autism spectrum disorder (OSD), bilingualism, and lack of psychosocial stimuli. Objectives: To determine the prevalence of delayed speech with and without hearing loss in children aged six months until three years. Methods: This study used 872 medical records of delayed speech children aged six months until three years with and without hearing loss in 2017 until 2020 period at Jala Puspa RSPAL Dr. Ramelan, Surabaya. The presence or absence of hearing loss was examined using Brainstem Evoked Response Audiometry (BERA), and the degree of hearing loss was examined using Auditory Steady-State Response (ASSR) test. Results: From a total of 872 medical records data studied, 558 (64.0%) were males and 314 (36.0%) were females. The majority (44.8%) of delayed speech children were from the two-year age group. There were 565 (64.8%) delayed speech children with hearing loss and 307 (35.2%) without hearing loss. Of those with hearing loss, 48.0% showed a profound degree. There was an increase in delayed speech children without hearing loss compared to those with hearing loss, from 1:2.04 in 2017 to 1:1.12 in 2020. Conclusion: There was an increase in delayed speech children without hearing loss compared to those with hearing loss.Keywords: Â ASSR, BERA, delayed speech, hearing loss